2021
DOI: 10.1177/2158244020988380
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Confirmation of Nation Brand Image in International Tourism Advertisement on Travel Intention of Foreign Tourists: The Case of Korean ITA for Chinese Tourists

Abstract: With the rapid growth of the international tourism industry, governments and tourism promotion agencies in various countries challenge to make more attractive international tourism advertisement (ITA) for foreign tourists to visit their countries. However, there may be difference in the degree to which each travel advertisement reflects the nation brand image. In some ITA cases, foreign tourists could not vividly highlight the unique images of the destination countries. Few studies have empirically validated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Past research found a BI effects consumer purchasing decisions, and many firms have invested heavily to build brand image. Consumers believe products with a high BI may enhance their self-image and achieve the role of promotion (Lee, 2021). Donnelly et al (2020) used UK fashion products as research products.…”
Section: Brand Image and Purchase Intentionmentioning
confidence: 99%
“…Past research found a BI effects consumer purchasing decisions, and many firms have invested heavily to build brand image. Consumers believe products with a high BI may enhance their self-image and achieve the role of promotion (Lee, 2021). Donnelly et al (2020) used UK fashion products as research products.…”
Section: Brand Image and Purchase Intentionmentioning
confidence: 99%
“…A notion also hypothesised by Pawaskar and Goel (2016) posits that information symmetry touchpoints influence the extrinsic travel motives of tourists by attracting them to specific destinations based on their attributes. The extant of literature (Avraham, 2020;Lee, 2021b;Lee et al, 2022;Matiza and Slabbert, 2020) also corroborates the NB's direct effect on tourist's travel motives, submitting that public perceptions of a country [via the NB] are a significant antecedent to tourists' conative behaviour, including their travel motives. This evidence aligns with the demand-oriented The destination marketing and media profile TE-A perspective of NB theory which supports the notion of inherent organic perceptions towards countries potentially exerting a direct predictive effect on consumptive decisionmaking.…”
Section: Hypothesis Developmentmentioning
confidence: 75%
“…Also, as identified earlier, nation branding and its role in shaping travel intention has been explored extensively (e.g., Chaulagain et al, 2019;Lee, 2021;Wu, 2017). When it comes to nation branding affecting other travel decisions however, a research gap becomes apparent.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The nation's own population have the greatest insight into their own country thus it is surprising that their perceptions of the nation have not been paired with the nation brand to determine its representativeness. Even the outcomes of nation branding tend to be explored externally rather than internally (e.g., Anholt, 1998;Fan, 2006;Lee, 2021). That is, while nations may understand the attitudinal and behavioural effects of branding their country for international audiences, the same attention has not been paid to understanding the effects of this for the nation's own population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation